Profile of salted fish processors in a socio-economic perspective in Ambesia Village, Tomini District, Parigi Moutong Regency - Massiseng, Andi Nur Apung; Ummung, Andi; Pildan, Nurlian; Hawati, Hawati; Jamil, Khairul (Sangia Research Media and Publishing, 2024)
This study was conducted to determine the socio-economic conditions of the foreign fish processing community in Ambesia Village, Tomini District, Parigi Motong Regency. This study was conducted in January 2024 - March 2024. A salted fish processor works in salted fish processing and knows the concept of salted fish processing principles. Salted fish processing activities include designing and implementing fisheries and offering salted fish prices. This study aims to determine the socio-economic conditions of salted fish processors in Ambesia Village, as well as to determine the prospects and obstacles in developing the salted fish business. Data collection was carried out using observation and interview methods, as well as questionnaires. Determination of respondents was carried out by census, namely taking the entire population consisting of 30 people from the salted fish processing community in Ambesia Village, Tomini District, Parigi Moutong Regency. In general, the economic conditions in Ambesia Village are supported by several types of alternative livelihoods for the community, such as fishermen, carpenters, laborers, civil servants, domestic helpers, mechanics, small entrepreneurs, traveling traders, and others. Constraints in the salted fish processing business are influenced by the availability of raw materials, low quality, and low level of education of salted fish processors. The profit of salted fish processors is Rp 3,754,346/month from the types of salted anchovies, lolosi, and dolo-dolo.